potete risolvere il 282… potete scrivere i passaggi. grazie🫶
3·SIN(x)^2 + 2·√3·SIN(x)·COS(x) + COS(x)^2 = 0
Υ = SIN(x)
Χ = COS(x)
Risolvo:
{3·Υ^2 + 2·√3·Υ·Χ + Χ^2 = 0
{Υ^2 + Χ^2 = 1
quindi:
{(√3·Υ + Χ)^2 = 0
{Υ^2 + Χ^2 = 1
procedo per sostituzione:
Υ = - √3·Χ/3
(- √3·Χ/3)^2 + Χ^2 = 1
4·Χ^2/3 = 1
Χ = - √3/2 ∨ Χ = √3/2
{Χ = - √3/2
{Υ = - √3·(- √3/2)/3
--------------------
{Χ = - √3/2
{Υ = 1/2
---------------
{COS(x) = - √3/2
{SIN(x) = 1/2
soluzione: [x = 5·pi/6]
------------------------
{Χ = √3/2
{Υ = - √3·(√3/2)/3
--------------------------
{Υ = - 1/2
{Χ = √3/2
------------
{SIN(x) = - 1/2
{COS(x) = √3/2
soluzione: [x = - pi/6]
In definitiva: x = - pi/6 + k·pi